Methodology of error measurements reduction while determining integrated errors of satellite nodes of planetary gears - Nasonov, Dmitry; Raevsky, Vladimir; Ilichev, Vladimir; Volkhonskaya, Anzhelika (Vibroengineering Procedia, 2021)
The mathematical model for definition of hole coordinates under satellites in cariage of planetary gear by results of indirect measurements is improved. Algorithm of revealing and elimination of incorrect initial data in automatic or manual mode is developed and implemented.